Variability in Dust Observed over China Using A-Train CALIOP Instrument - Hui Xu; Fengjie Zheng; Wenhao Zhang (Advances in Meteorology)
Patterns of dust aerosol variation over China are analyzed using A-Train CALIOP and precipitation, soil moisture, and vegetation coverage datasets during the period of 2007 and 2014. Spatially, dust is mostly prominent over northwestern China, with the highest and most widespread dust activities being in Taklimakan Desert. Dust is generally distributed across the atmosphere up to 5 km altitude, with a peak of DAFOD around 3 km. The dust layer has a significant geographical and seasonal drifting, with higher altitude in spring and summer and dust source regions (between 3 km and 5 km). Additionally, single dust layer is more often observed in a vertical column. Temporally, high amounts of dust aerosol (C-DAFOD as high as 0.08) experienced in spring subsequently continuous decrease until the spring of next year. The correlation coefficients between the latitude averaged column integrated dust aerosol feature optical depth (C-DAFOD) and precipitation, soil moisture, and vegetation coverage are −0.65, −0.81, and −0.77, respectively. The correlation coefficients of seasonal mean C-DAFOD with the three factors are −0.15, −0.67, and −0.35, respectively. The analysis showed dust and the other three factors are negatively correlated. Overall, dust over China shows considerable spatial, temporal, and vertical variations.